REPRESENTASI BUDAYA DALAM FILM SANG PENCERAH DAN SANG KIAI BERDASARKAN SUDUT PANDANG MAX WEBER - A Zahid (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The film is a spectacle that is highly favored by the public, a feature film presentation that gives a significant impact on the taste of choice in viewing, one of which is a heroic film. Not a few enthusiasts because it is thought to be a reflection of the services that have been inscribed by figures who are considered in the film world. Likewise, Khadaratus Syeh KH Hasyim Asy'ari and KH Ahmad Dahlan figures of the Muslim movement that underlies the largest organization in Indonesia, as well as the path of struggle during the colonial era is one of the very interesting paths to be examined. Besides his character as a national hero, these two figures as well as role models from Nahdatul Ulama-based organizations and Muhammadiyah have their own charismatics which in this study the researchers adopted as the aim of knowing how the charisma of the two major national figures in the film Sang Pencerah and Sang Kiai. The descriptive analysis method in this study is to describe the charismatic form of the two characters in the film, as an important analysis also in this study using scene analysis, to see the forms of charisma in the film. It can be concluded that the charisma attached to the figure of the kiai is very influential in influencing society more over the santri community, this happens in two different films, Sang Pencerah and Sang Kiai. All is not spared once again by the establishment of large organizations in Indonesia, namely Muhammadiah and Nahdatul Ulama (NU), so it is not surprising that the representation in this film is the charisma of the founder of Islamic organizations in Indonesia.